Chapter 6 Hermeneutics and Locality Hamlet in China - Glocalising Humanism, Glocalising Desire - Jiao, Min (Taylor & Francis, 2023)
"Hermeneutics and Locality: Hamlet in China, Glocalizing Humanism, Glocalizing Desire" explores the cultural mobility of Shakespeare through the lens of cultural hermeneutics, focusing on the intersection of locality studies and hermeneutic principles. One version of Hamlet produced in the Chinese Context, The Banquet (Feng, Xiaogang dir., 2006) will be explored to demonstrate how adaptations are heavily influenced, if not shaped by global critical interpretations of Hamlet, demonstrating the tenacity of literary effects between textuality and performance even in radical moments of change; on the other hand, it reveals that local and typical Chinese elements are mixed with western dramatic tradition, resulting in new connotations and potentials for global Shakespearean community.